Pilates Exercise OnPost PartumWomen With Pelvic Girdle Pain - Mona Oktarina (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Objective: To determine the effectof Pilates exercise on pain in post-partum women with pelvic girdle pain. Method: The research design used a pre-experimental design with one group pretest-posttest design. The population in this study were all postpartum women in Kuningan Barat sub-district, South Jakarta with complaints of pelvic girdle pain. The sampling technique in this study is non-probability method by purposive sampling in which the researcher took a sample based on predetermined criteria as many as 10 respondents. Pain data collection used the Visual Analog Scale and tested with the t test. Results: analysis of the dependent T test in postpartum women with pelvic girdle pain concluded that the pretest and posttest pain scores had a P-value (0.001) < ? 0.05, so H0 was rejected. Conclusion: Giving Pilates exercises can reduce pain in postpartum woman with pelvic girdle pain.